An Analysis of Code Mixing Used by Students in Learning English - Eka Maulidar; Bukhari Daud; Nurul Inayah (Universitas Syiah Kuala, 2020)
This research focused on analyzing the use code mixing in the terms of types and most dominant type used by students at SMA N 1 Bandar Baru. The objective of this study is to measure the frequency of code mixing occurrences and the most dominant type that students used. The research methodology used in this research was descriptive qualitative method. The subjects of this research were the students at SMA N 1 Bandar Baru. The subject are selected by using random sampling which the researcher randomly chooses the students from eleven grade. This research used observation in collecting the data. The researcher observed, recorded the data and take notes from the beginning until the end of the class. The data collection was done in three meetings a week and was take 90 minutes in one meeting. The result form observation shows that there were three types of code mixing used by students in in learning process, namely intra sentential code mixing , intra lexical code mixing and involving change of pronunciation. Intra sentential code mixing was the dominant type used by students in learning process, with total 72 utterances which is 61 utterances (85%) included intra sentential code mixing, 7 utterances (10%) included intra lexical and 4 utterances (5%) included Involving change of pronunciation.